Essays on modern slavery: disclosure, supply chain governance, and human rights violation consequences - Zafar, Faiza (2024)
This thesis provides a critical evaluation of corporate accountability for modern slavery, focusing on the most severe forms of labour exploitation in global supply chains. While corporate human rights abuse is not a recent issue, neoliberal economic policies have facilitated the lengthening of both labour and product supply chains through practices such as offshoring, subcontracting and outsourcing, allowing companies in Global North to distance themselves from the legal liability and diffuse responsibility for abuses in supply chains in Global South. More recently, however, the introduction of supply chain regulations, such as the UK Modern Slavery Act (2015), has unequivocally heightened and legally extended the notion of corporate accountability to include labour violations and modern forms of slavery in global supply chains. As a result, businesses are forced to take on greater responsibility for labour standards in their supply chains (Islam et al., 2023; Islam and Van Staden, 2022). Therefore, understanding how companies demonstrate accountability and transparency for modern slavery is a topical scholarly, practice and policy issue.